What is the Role of the Bystander Response in Radionuclide Therapies? - Brady, Darren; O'Sullivan, Joe M.; Prise, Kevin M. (Frontiers in Oncology, 2013)
Radionuclide therapy for cancer is undergoing a renaissance, with a wide range of radionuclide and clinical delivery systems currently under investigation. Dosimetry at the cellular and subcellular level is complex with inhomogeneity and incomplete targeting of all cells such that some tumour cells will receive little or no direct radiation energy. There is now sufficient preclinical evidence of a bystander response which can modulate the biology of these unirradiated cells with current research demonstrating both protective and inhibitory responses. Dependence upon fraction of irradiated cells has also been found has and the presence of functional gap junctions appears to be import for several bystander responses. The selection of either high or low LET radionuclides may be critical. While low LET radionuclides appear to have a bystander response proportional to dose, the dose-response from high LET radionuclides are more complex. In media transfer experiments a “U” shaped response curve has been demonstrated for high LET treatments. However this “U” shaped response has not been seen with co-culture experiments and its relevance remains uncertain. For high LET treatments there is a suggestion that dose rate effects may also be important with inhibitory effects noted with 125I labelling study and a stimulatory seen with 123I labelling in one study.